Isolation, Identification And Evaluation Of Antibacterial Activity Of The Semi-Purified Compound From Strobilanthes Crispus (L. Bremek) - Hamad Abou Muamar, Ahmed Faress (1999)
This study involved isolation, purification and identification of bioactive compound from the leaves of Kecibiling, Strobilanthes crispus. The bioactive compound obtained was tested for its antibacterial activity both in vitro and in vivo. Chemical investigation on the leaves using methanol, Column Chromatography and liquid- liquid extraction of the oily fraction resulted in the isolation, purification and identification of the active compound, verbascoside.